2012
DOI: 10.1523/jneurosci.2722-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Increased Excitability of Somatosensory Cortex in Aged Humans is Associated with Impaired Tactile Acuity

Abstract: Aging affects all levels of neural processing, including changes of intracortical inhibition and cortical excitability. Paired-pulse stimulation, the application of two stimuli in close succession, is a useful tool to investigate cortical excitability in humans. The paired-pulse behavior is characterized by the second response being significantly suppressed at short stimulus onset asynchronies. While in rat somatosensory cortex, intracortical inhibition has been demonstrated to decline with increasing age, dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
117
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 55 publications
(70 reference statements)
10
117
3
Order By: Relevance
“…Several recent studies (Hua et al, 2008; Leventhal et al, 2003; Stanley et al, 2012) have suggested a decline in GABAergic function with age and that is associated with a loss of function (Betts et al, 2007; Lenz et al, 2012; Leventhal et al, 2003; Wilson et al, 2011; Zhang et al, 2011). While GABA levels can be measured non-invasively in the human brain using magnetic resonance spectroscopy (MRS) (Puts and Edden, 2012), to date there has been a paucity of studies exploring the normal age-related variations in regional GABA levels…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies (Hua et al, 2008; Leventhal et al, 2003; Stanley et al, 2012) have suggested a decline in GABAergic function with age and that is associated with a loss of function (Betts et al, 2007; Lenz et al, 2012; Leventhal et al, 2003; Wilson et al, 2011; Zhang et al, 2011). While GABA levels can be measured non-invasively in the human brain using magnetic resonance spectroscopy (MRS) (Puts and Edden, 2012), to date there has been a paucity of studies exploring the normal age-related variations in regional GABA levels…”
Section: Introductionmentioning
confidence: 99%
“…16,25,26,52 This study aimed to investigate intracortical inhibition of the primary somatosensory cortex (S1), as measured by paired-pulse suppression (PPS) ratio of the N20m-P35m response, in patients with FM by using pairedpulse median nerve stimulation and magnetoencephalography (MEG). We hypothesized that intracortical inhibition of the S1 would be reduced in patients with FM, ie, patients with FM would demonstrate higher PPS ratios than healthy control (HC) subjects, and that the higher reductions of inhibition would be associated with increased clinical pain.…”
Section: Introductionmentioning
confidence: 99%
“…Although some effects of age and disease on the SEP after median nerve stimulation have been reported (Allison et al, 1984;Ugawa et al, 1996;Lenz et al, 2012), this may be the first systematic study of the relationship between RF and aging.…”
Section: Discussionmentioning
confidence: 92%
“…In 2012, Lenz et al used a paired stimulation interval of only one ISI on elderly human subjects and found a reduction in SEP suppression (Lenz et al, 2012). Systematic studies of aging effects on inhibitory neural activity in somatosensory evoked responses have not yet been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation